Margery Kempe and the lonely reader - Krug, Rebecca (Cornell University Press, 2017)
Comfort – Despair – Shame – Fear – Loneliness
Includes bibliographical references and index
Keywords: Kempe; Margery; Book of Margery Kempe; Christian women; Women authors; English; Christian pilgrims and pilgrimages